Banana blossom agar (BABA), a new medium to isolate members of the Cryptococcus neoformans/Cryptococcus gattii species complex useful for resource limited countries - Kantarawee Khayhan (2018)
© 2018 Blackwell Verlag GmbH Isolation of representatives of the Cryptococcus neoformans/Cryptococcus gattii species complex can be made using dopamine containing media, such as Niger seed agar and l-DOPA agar. Here, we describe an alternative medium that uses banana flowers. Banana is a dopamine containing fruit and is widely available in tropical and subtropical countries that have high numbers of cryptococcosis patients. This banana blossom-based agar is useful for the enrichment of isolates of the C. neoformans/C. gattii species complex from environmental and clinical materials. The banana blossom agar (BABA) with and without creatinine can differentiate between the melanin forming isolates of the C. neoformans/C. gattii species complex from other yeasts that do not form melanin.